2022
DOI: 10.1111/epi.17231
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset refractory status epilepticus as an early manifestation of multisystem inflammatory syndrome in adults after COVID‐19

Abstract: Multisystem inflammatory syndrome in adults (MIS‐A) is a rare hyperinflammatory complication with multi‐organ involvement that manifests a few weeks after recovering from a typically mild coronavirus disease 2019 (COVID‐19) infection. Although encephalopathy and seizures can occur in the acute phase of COVID‐19, the nervous system is infrequently involved in patients with MIS‐A. Herein, we describe the case of a young woman who presented with new‐onset refractory status epilepticus (NORSE) following a mild COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Although NORSE has not been reported as a presenting symptom in MIS-C, it has been reported in adults with multisystem inflammatory syndrome (MIS-A). 9 Nawfal et al 10 reported the first case of NORSE in MIS-A, in a 21-year-old woman with cardiac, gastrointestinal dysfunction, and encephalopathy, occurring 5 weeks after her COVID-19 infection. Leelamani et al 11 reported another young lady with NORSE 2 days after developing mild fever and cough and having a positive nasal swab PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although NORSE has not been reported as a presenting symptom in MIS-C, it has been reported in adults with multisystem inflammatory syndrome (MIS-A). 9 Nawfal et al 10 reported the first case of NORSE in MIS-A, in a 21-year-old woman with cardiac, gastrointestinal dysfunction, and encephalopathy, occurring 5 weeks after her COVID-19 infection. Leelamani et al 11 reported another young lady with NORSE 2 days after developing mild fever and cough and having a positive nasal swab PCR.…”
Section: Discussionmentioning
confidence: 99%
“…16 Finally, systemic capillary leak syndrome, spontaneous coronary artery dissection, severe inflammatory myopathy, cortical unihemispheric brain edema, thyroiditis, refractory status epilepticus, ischemic stroke, and subconjunctival hemorrhage have been rarely reported as clinical manifestations of MIS-A. 28,30,31,[61][62][63] Overall, the clinical features of MIS-A, including fever, gastrointestinal, and cardiovascular involvement, are similar to those of MIS-C. 16,19,53 These findings were consistent with the comparisons between Belay et al 53,60 report about MIS-A and previous surveillance data about MIS-C. Compared to patients with MIS-C (n = 1733) from previously published surveillance data, a higher proportion of the patients with MIS-A (n = 20) had shock (75% vs. 37%), cardiac dysfunction (75% vs. 31%), myocarditis (70% vs. 17%), and pericardial effusion (45% vs. 23%).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Uncommonly, 9 (5%) of 195 patients had arterial or venous thrombosis, and 1 had severe mononeuritis multiplex, affecting the right median and facial nerves and both ulnar, tibial, peroneal, and sural nerves 16 . Finally, systemic capillary leak syndrome, spontaneous coronary artery dissection, severe inflammatory myopathy, cortical unihemispheric brain edema, thyroiditis, refractory status epilepticus, ischemic stroke, and subconjunctival hemorrhage have been rarely reported as clinical manifestations of MIS‐A 28,30,31,61–63 …”
Section: Clinical Manifestationsmentioning
confidence: 99%